Anti-settling high-thermal-conductivity pouring sealant and preparation method thereof

By using an anti-settling agent composed of ultrafine powder, treatment agent and end vinyl polydimethylsiloxane in the thermally conductive potting glue, the problem of sedimentation of thermally conductive potting glue is solved, and the uniformity of thermal conductivity and Efficient heat dissipation of electronic components.

CN119463804APending Publication Date: 2025-02-18SHENZHEN AOCHUAN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411803420.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing thermally conductive potting glue is prone to settlement during storage and use, resulting in uneven thermal conductivity and affecting the overall heat dissipation effect of the component.

Method used

An anti-settling agent composed of ultrafine powder, treatment agent and end vinyl polydimethylsiloxane is used to ensure that the thermally conductive filler is stable suspended in the silicone oil matrix, and the settlement of large particles of thermally conductive filler is directly inhibited by physical filling and increasing viscosity.

Benefits of technology

The stable suspension of thermally conductive fillers is achieved, uneven thermal conductivity caused by settlement, improve the heat dissipation efficiency of electronic components, and maintain good anti-settlement performance during long-term storage and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463804A_ABST
    Figure CN119463804A_ABST
Patent Text Reader

Abstract

The invention provides an anti-settling high-thermal-conductivity pouring sealant and a preparation method thereof. The pouring sealant is formed by mixing a first component and a second component; the first component is prepared from the following raw materials in parts by mass: 2 to 8 parts of vinyl-terminated polydimethylsiloxane, 1 to 10 parts of anti-settling agent, 90 to 98 parts of modified heat-conducting filler and 0.1 to 1 part of platinum catalyst; the second component is prepared from the following raw materials in parts by mass: 1 to 6 parts of vinyl-terminated polydimethylsiloxane, 1 to 10 parts of anti-settling agent, 90 to 98 parts of modified heat-conducting filler, 0.1 to 1 part of inhibitor, 1 to 6 parts of hydrogen-terminated polydimethylsiloxane and 1 to 6 parts of methyl-terminated methylhydrosiloxane; wherein the anti-settling agent is prepared from the following raw materials in parts by mass: 50 to 75 parts of superfine powder, 0.2 to 2 parts of treating agent and 25 to 50 parts of vinyl-terminated polydimethylsiloxane. The pouring sealant provided by the invention has excellent heat-conducting property, anti-settling property and good processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal conductive materials, and in particular to an anti-settling and high thermal conductive potting glue and a preparation method thereof. Background Art

[0002] As electronic devices continue to become smaller, more integrated, and more powerful, the heating problem of devices is becoming increasingly serious. In order to ensure that electronic components can dissipate heat efficiently and maintain long-term stable operation, the importance of thermal conductive materials in thermal management systems is increasing.

[0003] Thermally conductive potting compound is a commonly used thermally conductive material, usually composed of a base material (such as silicone resin, epoxy resin, etc.) and a thermally conductive filler (such as aluminum oxide, boron nitride, magnesium oxide, etc.). Thermally conductive potting compound can fill tiny gaps between electronic components, and at the same time efficiently transfer the heat of electronic components to the radiator or the environment to avoid local overheating. It can also provide components with anti-vibration, moisture-proof, dust-proof and other protections through potting, thereby improving the overall mechanical properties.

[0004] However, existing thermally conductive potting glue is prone to sedimentation during storage and use, resulting in uneven thermal conductivity, affecting the overall heat dissipation effect of the component, and also causing the fluidity of the material to deteriorate, making it difficult to stir evenly, bringing challenges to production and operation. Summary of the invention

[0005] In view of the above-mentioned problems, the present application is proposed to provide an anti-settling high thermal conductivity potting adhesive and a preparation method thereof that overcomes the above-mentioned problems or at least partially solves the above-mentioned problems, including:

[0006] An anti-settling and high-thermal-conductivity potting adhesive is prepared by mixing a first component and a second component;

[0007] The first component comprises the following raw materials by weight: 2-8 parts of vinyl-terminated polydimethylsiloxane, 1-10 parts of an anti-settling agent, 90-98 parts of a modified thermally conductive filler, and 0.1-1 parts of a platinum catalyst;

[0008] The second component comprises the following raw materials by mass: 1-6 parts of vinyl-terminated polydimethylsiloxane, 1-10 parts of anti-settling agent, 90-98 parts of modified thermal conductive filler, 0.1-1 parts of inhibitor, 1-6 parts of hydrogen-terminated polydimethylsiloxane and 1-6 parts of methyl-terminated methylhydrogensiloxane;

[0009] The anti-settling agent comprises the following raw materials by weight: 50-75 parts of ultrafine powder, 0.2-2 parts of treating agent and 25-50 parts of vinyl-terminated polydimethylsiloxane; the particle size of the ultrafine powder is less than 1 μm.

[0010] Preferably, the ultrafine powder includes at least one of silicon dioxide, glass fiber, aluminum oxide, aluminum hydroxide and zinc oxide.

[0011] Preferably, the modified thermally conductive filler comprises the following raw materials in parts by mass: 98-99.8 parts of thermally conductive filler and 0.2-2 parts of treating agent.

[0012] Preferably, the thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, aluminum hydroxide, zinc oxide and diamond.

[0013] Preferably, the treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.

[0014] Preferably, the treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, and single-ended trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.

[0015] Preferably, the viscosity of the vinyl-terminated polydimethylsiloxane is 40-110 mPa·s, and the vinyl content is 0.9-2.1 wt %; the hydrogen content of the hydrogen-terminated polydimethylsiloxane is 0.1-0.36 wt %; and the hydrogen content of the methyl-terminated methylhydrogensiloxane is 0.1-0.36 wt %.

[0016] A method for preparing the potting compound as described in any one of the above items, comprising:

[0017] The modified thermal conductive filler, the anti-settling agent, the vinyl-terminated polydimethylsiloxane and the platinum catalyst are stirred and mixed according to a proportion to obtain a first component;

[0018] The modified thermal conductive filler, the anti-settling agent, the vinyl-terminated polydimethylsiloxane, the hydrogen-terminated polydimethylsiloxane, the methyl-terminated methylhydrogensiloxane and the inhibitor are stirred and mixed according to the proportion to obtain the second component.

[0019] Preferably, it also includes:

[0020] The thermal conductive filler and the treating agent are stirred and mixed according to a proportion to obtain a modified thermal conductive filler.

[0021] Preferably, it also includes:

[0022] The ultrafine powder, the treating agent and the vinyl-terminated polydimethylsiloxane are stirred and mixed according to a proportion to obtain an anti-settling agent.

[0023] This application has the following advantages:

[0024] In view of the problem that existing thermally conductive potting glue is prone to sedimentation, the present application provides a solution that uses ultrafine powder, a treating agent and an anti-settling agent composed of vinyl-terminated polydimethylsiloxane to ensure that the thermally conductive filler is stably suspended in a silicone oil matrix, specifically: an anti-settling and high-thermal conductive potting glue, which is mixed with a first component and a second component; the first component includes the following raw materials by mass: 2-8 parts of vinyl-terminated polydimethylsiloxane, 1-10 parts of an anti-settling agent, 90-98 parts of a modified thermally conductive filler and 0.1-1 parts of a platinum catalyst. parts; the second component includes the following raw materials in parts by mass: 1-6 parts of vinyl-terminated polydimethylsiloxane, 1-10 parts of anti-settling agent, 90-98 parts of modified thermal conductive filler, 0.1-1 parts of inhibitor, 1-6 parts of hydrogen-terminated polydimethylsiloxane and 1-6 parts of methyl-terminated methylhydrogensiloxane; wherein the anti-settling agent includes the following raw materials in parts by mass: 50-75 parts of ultrafine powder, 0.2-2 parts of treating agent and 25-50 parts of vinyl-terminated polydimethylsiloxane; the particle size of the ultrafine powder is less than 1 μm.

[0025] Both the first component and the second component contain 90-98 parts by weight of modified thermally conductive filler, ensuring that the thermal conductivity of the system reaches an excellent level; by adopting 50-75 parts by weight of ultrafine powder, 0.2-2 parts by weight of treating agent and 25-50 parts by weight of terminal vinyl polydimethylsiloxane composed of anti-settling agent, it can be ensured that the thermally conductive filler is stably suspended in the silicone oil matrix, wherein the ultrafine powder can directly inhibit the sedimentation of large-particle thermally conductive filler by physical filling and increasing viscosity, the treating agent can optimize the dispersibility of the ultrafine powder and the interfacial compatibility with the silicone oil matrix, avoiding the failure of the anti-settling agent due to self-agglomeration or sedimentation, and the terminal vinyl polydimethylsiloxane can enhance the dispersion and wetting effect of the anti-settling agent in the silicone oil system, ensuring its long-lasting function.

[0026] The potting compound provided in the present application has excellent thermal conductivity, anti-settling performance and good processing performance. Its thermal conductivity is as high as 2.5 to 5 W / m·K, which can effectively improve the heat dissipation efficiency of electronic components and prevent performance degradation caused by overheating of components. At the same time, it exhibits extremely strong anti-settling performance during long-term storage and use, which can avoid uneven heat conduction caused by sedimentation of thermally conductive fillers. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the description of the present application will be briefly introduced below. Obviously, the drawings described below are only part of the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 It is a flow chart of the steps of the first part of the method for preparing a potting compound provided in one embodiment of the present application;

[0029] Figure 2 It is a flow chart of the steps of the second part of the method for preparing a potting compound provided in one embodiment of the present application;

[0030] Figure 3 This is a flow chart of the steps of the third part of the method for preparing potting glue provided in one embodiment of the present application. DETAILED DESCRIPTION

[0031] In order to make the purpose, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0032] By analyzing the prior art, the inventors found that the existing thermally conductive potting materials mainly improve thermal conductivity by filling thermally conductive fillers. In order to ensure good thermal conductivity, a large amount of thermally conductive fillers need to be filled into the silicone oil matrix. However, the thermally conductive fillers are mainly composed of larger particles. During storage and use, they are prone to sedimentation due to gravity, resulting in uneven thermal conductivity, affecting the overall heat dissipation effect of the components, and also resulting in poor fluidity of the material, making it difficult to stir evenly, bringing challenges to production and operation.

[0033] In one embodiment of the present application, a potting adhesive with anti-settling and high thermal conductivity is provided, which is formed by mixing a first component and a second component;

[0034] The first component comprises the following raw materials by weight: 2-8 parts of vinyl-terminated polydimethylsiloxane, 1-10 parts of an anti-settling agent, 90-98 parts of a modified thermally conductive filler, and 0.1-1 parts of a platinum catalyst;

[0035] The second component comprises the following raw materials by mass: 1-6 parts of vinyl-terminated polydimethylsiloxane, 1-10 parts of anti-settling agent, 90-98 parts of modified thermal conductive filler, 0.1-1 parts of inhibitor, 1-6 parts of hydrogen-terminated polydimethylsiloxane and 1-6 parts of methyl-terminated methylhydrogensiloxane;

[0036] The anti-settling agent comprises the following raw materials by weight: 50-75 parts of ultrafine powder, 0.2-2 parts of treating agent and 25-50 parts of vinyl-terminated polydimethylsiloxane; the particle size of the ultrafine powder is less than 1 μm.

[0037] Both the first component and the second component contain 90-98 parts by weight of modified thermally conductive filler, ensuring that the thermal conductivity of the system reaches an excellent level; by adopting 50-75 parts by weight of ultrafine powder, 0.2-2 parts by weight of treating agent and 25-50 parts by weight of terminal vinyl polydimethylsiloxane composed of anti-settling agent, it can be ensured that the thermally conductive filler is stably suspended in the silicone oil matrix, wherein the ultrafine powder can directly inhibit the sedimentation of large-particle thermally conductive filler by physical filling and increasing viscosity, the treating agent can optimize the dispersibility of the ultrafine powder and the interfacial compatibility with the silicone oil matrix, avoiding the failure of the anti-settling agent due to self-agglomeration or sedimentation, and the terminal vinyl polydimethylsiloxane can enhance the dispersion and wetting effect of the anti-settling agent in the silicone oil system, ensuring its long-lasting function.

[0038] The potting glue provided in this embodiment has excellent thermal conductivity, anti-settling performance and good processing performance. Its thermal conductivity is as high as 2.5-5W / m·K, which can effectively improve the heat dissipation efficiency of electronic components and prevent performance degradation caused by overheating of components. At the same time, it exhibits extremely strong anti-settling performance during long-term storage and use, which can avoid uneven heat conduction caused by sedimentation of thermally conductive fillers.

[0039] Next, the potting compound in this exemplary embodiment will be further described.

[0040] In one embodiment of the present application, the ultrafine powder is pre-dispersed to break the agglomeration between the ultrafine powders due to the intermolecular force, so as to help the powders to better react with the treatment agent and disperse in the silicone oil matrix.

[0041] In one embodiment of the present application, the ultrafine powder includes at least one of silicon dioxide, glass fiber, aluminum oxide, aluminum hydroxide and zinc oxide. The ultrafine powder of the above type has good electrical insulation and chemical stability.

[0042] In one embodiment of the present application, the modified thermally conductive filler comprises the following raw materials by weight: 98-99.8 parts of thermally conductive filler and 0.2-2 parts of treating agent. The modified thermally conductive filler is obtained by surface modification of the thermally conductive filler. The surface treatment of the treating agent can ensure that the thermally conductive filler is evenly dispersed to avoid agglomeration or sedimentation.

[0043] In one embodiment of the present application, the thermally conductive filler is pre-dispersed to break the agglomeration of the thermally conductive filler due to the intermolecular force, thereby helping the filler to better react with the treatment agent and disperse in the silicone oil matrix.

[0044] In one embodiment of the present application, the thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, aluminum hydroxide, zinc oxide and diamond. The above-mentioned thermally conductive fillers have good thermal conductivity, electrical insulation and chemical stability.

[0045] In one embodiment of the present application, the treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, single-ended trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.

[0046] In a preferred embodiment of the present application, the treatment agent includes at least one of y-(2,3-epoxypropoxy)propyl trimethoxysilane, y-methacryloxypropyl trimethoxysilane, dodecyl trimethoxy silicone oil, dodecyl triethoxysilane, hexadecyl trimethoxysilane, and hexadecyl triethoxysilane, and at least one of single-terminal trimethyl / ethoxysilane-terminated polydimethyl silicone oil and polyether-modified polydimethylsiloxane. It should be noted that the molecular weight of y-(2,3-epoxypropoxy)propyl trimethoxysilane, y-methacryloxypropyl trimethoxysilane, dodecyl trimethoxy silicone oil, dodecyl triethoxysilane, hexadecyl trimethoxysilane, and hexadecyl triethoxysilane is relatively low, while the molecular weight of single-terminal trimethyl / ethoxysilane-terminated polydimethyl silicone oil and polyether-modified polydimethylsiloxane is relatively high. By combining treatment agents with different molecular weights, a layer of steric hindrance can be formed on the surface of ultrafine powder and thermal conductive filler to avoid direct contact between powder and filler, thereby effectively weakening the aggregation effect between powder and filler.

[0047] In a preferred embodiment of the present application, the treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane and y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, at least one of single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane, and at least one of single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane. It should be noted that y-(2,3-epoxypropoxy)propyltrimethoxysilane and y-methacryloxypropyltrimethoxysilane can eliminate hydroxyl groups on the surface of fillers and powders through chemical reactions, thereby reducing agglomeration; long-chain alkyl groups such as dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane and hexadecyltriethoxysilane can increase the hydrophobicity of fillers and powders, and enhance the interfacial bonding strength between fillers and powders and the silicone oil matrix; high molecular weight compounds such as single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane can increase lubricity and polar compatibility, and improve the dispersion stability of fillers and powders in polar matrices. By combining treatment agents of different types and molecular weights, the hydroxyl groups on the surface of thermally conductive fillers and ultrafine powders can be eliminated to reduce the adsorption tendency between particles. The surface chemical properties of thermally conductive fillers and ultrafine powders can also be improved to enhance their interfacial bonding with the matrix material. At the same time, a layer of steric hindrance can be formed on the surface of thermally conductive fillers and ultrafine powders to effectively weaken the aggregation effect between fillers and powders, thereby ensuring that the thermally conductive fillers and ultrafine powders are evenly dispersed and avoiding agglomeration or sedimentation.

[0048] In one embodiment of the present application, the viscosity of the vinyl-terminated polydimethylsiloxane is 40-110 mPa·s, and the vinyl content is 0.9-2.1 wt%. The viscosity of the vinyl-terminated polydimethylsiloxane is 40-110 mPa·s, which is beneficial to the fluidity of the material, facilitates mixing and uniform dispersion, and improves the coating and filling effects of the potting glue; the vinyl content is 0.9-2.1 wt%, which can effectively control the crosslinking density of the addition reaction and ensure that the material has good mechanical properties after curing.

[0049] As an example, the vinyl-terminated polydimethylsiloxane includes at least one of a vinyl-terminated polydimethylsiloxane having a viscosity of 40-60 mPa·s and a vinyl content of 1.9-2.1 wt %, a vinyl-terminated polydimethylsiloxane having a viscosity of 70-90 mPa's and a vinyl content of 1.1-1.2 wt %, and a vinyl-terminated polydimethylsiloxane having a viscosity of 90-110 mPa·s and a vinyl content of 0.9-1.0 wt %.

[0050] In one embodiment of the present application, the hydrogen content of the hydrogen-terminated polydimethylsiloxane is 0.1-0.36wt%; the hydrogen content of the methyl-terminated methylhydrogensiloxane is 0.1-0.36wt%. The hydrogen content of the hydrogen-terminated polydimethylsiloxane is 0.1-0.36wt%, and the hydrogen content of the methyl-terminated methylhydrogensiloxane is 0.1-0.36wt%, which can ensure that the addition reaction with the vinyl-terminated polydimethylsiloxane is fully carried out, and avoid the degradation of material performance caused by incomplete reaction.

[0051] As an example, the hydrogen-terminated polydimethylsiloxane includes at least one of hydrogen-terminated polydimethylsiloxanes having a hydrogen content of 0.1-0.12wt%, a hydrogen content of 0.16-0.19wt%, and a hydrogen content of 0.32-0.36wt%; the methyl-terminated methylhydrogensiloxane includes at least one of methyl-terminated methylhydrogensiloxanes having a hydrogen content of 0.1-0.12wt%, a hydrogen content of 0.16-0.19wt%, and a hydrogen content of 0.32-0.36wt%.

[0052] In one embodiment of the present application, the inhibitor includes at least one of a polyvinyl small molecule and ethynyl cyclohexanol. By introducing a polyvinyl small molecule or ethynyl cyclohexanol inhibitor, the silicone oil material in the second component can be prevented from being cross-linked prematurely, and the rate of the cross-linking reaction can be effectively regulated after the first component and the second component are mixed, ensuring sufficient operating time.

[0053] Reference Figure 1 In one embodiment of the present application, a method for preparing the potting compound as described in any of the above embodiments is provided, comprising:

[0054] S110, stirring and mixing the modified thermal conductive filler, the anti-settling agent, the vinyl-terminated polydimethylsiloxane and the platinum catalyst according to a proportion to obtain a first component;

[0055] S120, mixing the modified thermal conductive filler, the anti-settling agent, the vinyl-terminated polydimethylsiloxane, the hydrogen-terminated polydimethylsiloxane, the methyl-terminated methylhydrogensiloxane and the inhibitor according to a proportion to obtain a second component.

[0056] Next, the preparation method of the potting compound in this exemplary embodiment will be further described.

[0057] As described in step S110, the modified thermal conductive filler, the anti-settling agent, the vinyl-terminated polydimethylsiloxane and the platinum catalyst are stirred and mixed according to a proportion to obtain a first component.

[0058] The modified thermal conductive filler, anti-settling agent, vinyl-terminated polydimethylsiloxane and platinum catalyst are put into a reaction kettle according to the proportion, dispersed evenly with a planetary mixer (stirring rate of 15-40 Hz, dispersion rate of 400-1000 Hz, stirring time of 2 h), and mixed to obtain the first component.

[0059] As described in step S120, the modified thermal conductive filler, the anti-settling agent, the vinyl-terminated polydimethylsiloxane, the hydrogen-terminated polydimethylsiloxane, the methyl-terminated methylhydrogensiloxane and the inhibitor are stirred and mixed according to the proportion to obtain a second component.

[0060] The modified thermal conductive filler, anti-settling agent, vinyl-terminated polydimethylsiloxane, hydrogen-terminated polydimethylsiloxane, methyl-terminated methylhydrogensiloxane and inhibitor were put into a reaction kettle according to the proportion, dispersed evenly with a planetary mixer (stirring rate of 15-40 Hz, dispersion rate of 400-1000 Hz, stirring time of 2 h), and mixed to obtain the second component.

[0061] Reference Figure 2 In one embodiment of the present application, the method further includes:

[0062] S010, stirring and mixing the thermal conductive filler and the treating agent according to a proportion to obtain a modified thermal conductive filler.

[0063] The thermal conductive filler is put into a high-speed mixer according to the ratio, and first dispersed and mixed (the equipment speed is 10-40Hz, the time is 1-5min), and then the treatment agent is added, and then high-speed dispersed and mixed (the equipment speed is 10-40Hz, the time is 3-10min) to obtain a modified thermal conductive filler.

[0064] Reference Figure 3 In one embodiment of the present application, the method further includes:

[0065] S020. Mix the ultrafine powder, the treating agent and the vinyl-terminated polydimethylsiloxane according to a proportion to obtain an anti-settling agent.

[0066] The ultrafine powder is placed in a high-speed disperser, and first dispersed and mixed (the equipment speed is 10-40Hz, and the time is 1-5min), and then the treatment agent is added, and then high-speed dispersed and mixed (the equipment speed is 10-40Hz, and the time is 3-10min). The treated powder is added to the terminal vinyl polydimethylsiloxane, and dispersed evenly with a planetary mixer (stirring rate is 15-40Hz, dispersion rate is 200-400Hz, and stirring time is 0.5-2h) to obtain an anti-settling agent.

[0067] The specific embodiments and experimental data of this application are as follows:

[0068] Embodiment 1

[0069] An anti-settling and high-thermal-conductivity potting adhesive is prepared by mixing a first component and a second component;

[0070] The first component includes the following raw materials by mass: 9 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 90-110 mPa·s, 2 parts of an anti-settling agent, 88.8 parts of a modified thermal conductive filler, and 0.2 parts of a platinum catalyst;

[0071] The second component includes the following raw materials by mass: 6 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 90-110 mPa·s, 2 parts of anti-settling agent, 88 parts of modified thermal conductive filler, 0.1 parts of inhibitor, 2 parts of hydrogen-terminated polydimethylsiloxane with a hydrogen content of 0.12wt%, and 1.9 parts of methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.1wt%;

[0072] The modified thermal conductive filler includes the following raw materials by mass: 30 parts of spherical alumina with a particle size of 40 μm, 30 parts of aluminum hydroxide with a particle size of 50 μm, 35 parts of quasi-spherical alumina with a particle size of 5 μm, 14.5 parts of quasi-spherical alumina with a particle size of 3 μm, 0.2 parts of dodecyl trimethoxysiloxane, and 0.3 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil;

[0073] The anti-settling agent includes the following raw materials by mass: 50 parts of alumina powder with a particle size of 0.6 μm, 20 parts of aluminum hydroxide powder with a particle size of 1 μm, 0.4 parts of dodecyltrimethoxysiloxane, 0.6 parts of single-end trimethoxysilane-terminated polydimethylsiloxane, and 29 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 90-110 mPa·s.

[0074] The preparation method of the above-mentioned potting glue comprises:

[0075] By mass, 30 parts of spherical alumina with a particle size of 40 μm, 30 parts of aluminum hydroxide with a particle size of 50 μm, 35 parts of quasi-spherical alumina with a particle size of 5 μm, and 14.5 parts of quasi-spherical alumina with a particle size of 3 μm were put into a high-speed mixer for mixing (the equipment speed was 10 Hz, and the time was 1 min), 0.2 parts of dodecyltrimethoxysiloxane and 0.3 parts of single-end trimethoxysilane-terminated polydimethylsilicone were added, and then dispersed and mixed at a high speed (the equipment speed was 25 Hz, and the time was 5 min) to obtain a modified thermally conductive filler;

[0076] By mass, 50 parts of alumina powder with a particle size of 0.6 μm and 20 parts of aluminum hydroxide powder with a particle size of 1 μm were placed in a high-speed disperser for mixing (the equipment speed was 10 Hz and the time was 1 min), 0.4 parts of dodecyl trimethoxysiloxane and 0.6 parts of single-end trimethoxysilane-terminated polydimethylsilicone were added, and then dispersed and mixed at a high speed (the equipment speed was 25 Hz and the time was 5 min), and the treated powder was added to 29 parts of terminal vinyl polydimethylsiloxane with a viscosity of 90-110 mPa·s, and dispersed evenly with a planetary mixer (stirring rate was 15 Hz, dispersion rate was 200 Hz, and stirring time was 0.5 h) to obtain an anti-settling agent;

[0077] 9 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 90-110 mPa·s, 2 parts of an anti-settling agent, 88.8 parts of a modified thermally conductive filler, and 0.2 parts of a platinum catalyst were added into a reaction kettle by weight, and dispersed evenly with a planetary mixer (stirring rate of 15 Hz, dispersion rate of 800 Hz, stirring time of 2 h), and mixed to obtain a first component;

[0078] 6 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 90-110 mPa·s, 2 parts of an anti-settling agent, 88 parts of a modified thermally conductive filler, 0.1 parts of an inhibitor, 2 parts of hydrogen-terminated polydimethylsiloxane with a hydrogen content of 0.12 wt%, and 1.9 parts of methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.1 wt% were added into a reaction kettle, and dispersed evenly with a planetary mixer (stirring rate of 15 Hz, dispersion rate of 800 Hz, stirring time of 2 h), and mixed to obtain a second component;

[0079] The prepared first component and second component are mixed in a mass ratio of 1:1 for use.

[0080] Embodiment 2

[0081] An anti-settling and high-thermal-conductivity potting adhesive is prepared by mixing a first component and a second component;

[0082] The first component includes the following raw materials by mass: 5 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 70-90 mPa·s, 2 parts of an anti-settling agent, 92.8 parts of a modified thermal conductive filler, and 0.2 parts of a platinum catalyst;

[0083] The second component includes the following raw materials by mass: 3 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 70-90 mPa·s, 2 parts of anti-settling agent, 92.8 parts of modified thermal conductive filler, 0.2 parts of inhibitor, 1 part of hydrogen-terminated polydimethylsiloxane with a hydrogen content of 0.18wt%, and 1 part of methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.1wt%;

[0084] The modified thermal conductive filler includes the following raw materials by mass: 40 parts of spherical alumina with a particle size of 70 μm, 10 parts of aluminum hydroxide with a particle size of 50 μm, 35 parts of spherical alumina with a particle size of 10 μm, 14.6 parts of quasi-spherical alumina with a particle size of 3 μm, 0.2 parts of dodecyl triethoxysiloxane, 0.1 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil, and 0.1 parts of octadecyl trimethoxysilane;

[0085] The anti-settling agent includes the following raw materials by mass: 40 parts of silicon dioxide powder with a particle size of 1 μm, 40 parts of aluminum oxide powder with a particle size of 1 μm, 0.4 parts of dodecyl triethoxysiloxane, 0.3 parts of single-end trimethoxysilane-terminated polydimethyl silicone oil, 0.3 parts of octadecyl trimethoxy, and 19 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 70-90 mPa·s.

[0086] The preparation method of the above-mentioned potting glue comprises:

[0087] By mass, 40 parts of spherical alumina with a particle size of 70 μm, 10 parts of aluminum hydroxide with a particle size of 50 μm, 35 parts of spherical alumina with a particle size of 10 μm, and 14.6 parts of quasi-spherical alumina with a particle size of 3 μm were put into a high-speed mixer for mixing (the equipment speed was 10 Hz, and the time was 1 min), 0.2 parts of dodecyl triethoxysiloxane, 0.1 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil, and 0.1 parts of octadecyl trimethoxy were added, and then dispersed and mixed at a high speed (the equipment speed was 30 Hz, and the time was 6 min) to obtain a modified thermally conductive filler;

[0088] By mass, 40 parts of 1 μm silica powder, 40 parts of 1 μm alumina powder, and 0.4 parts of dodecyl triethoxysiloxane were put into a high-speed disperser for mixing (equipment speed was 10 Hz, time was 1 min), 0.4 parts of dodecyl triethoxysiloxane, 0.3 parts of single-end trimethoxysilane-terminated polydimethylsilicone, and 0.3 parts of octadecyl trimethoxy were added, and then dispersed and mixed at high speed (equipment speed was 30 Hz, time was 6 min), and the treated powder was added to 19 parts of 70-90 mPa·s viscosity of terminal vinyl polydimethylsiloxane, and dispersed evenly with a planetary mixer (stirring rate was 20 Hz, dispersion rate was 300 Hz, and stirring time was 0.5 h) to obtain an anti-settling agent;

[0089] 5 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 70-90 mPa·s, 2 parts of an anti-settling agent, 92.8 parts of a modified thermally conductive filler, and 0.2 parts of a platinum catalyst were added into a reaction kettle by weight, and dispersed evenly with a planetary mixer (stirring rate of 25 Hz, dispersion rate of 1000 Hz, stirring time of 1.5 h), and mixed to obtain a first component;

[0090] 3 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 70-90 mPa·s, 2 parts of anti-settling agent, 92.8 parts of modified thermal conductive filler, 0.2 parts of inhibitor, 1 part of hydrogen-terminated polydimethylsiloxane with a hydrogen content of 0.18 wt%, and 1 part of methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.1 wt% were added into a reaction kettle, and dispersed evenly with a planetary mixer (stirring rate of 25 Hz, dispersion rate of 1000 Hz, stirring time of 1.5 h), and mixed to obtain a second component;

[0091] The prepared first component and second component are mixed in a mass ratio of 1:1 for use.

[0092] Embodiment 3

[0093] An anti-settling and high-thermal-conductivity potting adhesive is prepared by mixing a first component and a second component;

[0094] The first component includes the following raw materials by mass: 3.8 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60 mPa·s, 1.5 parts of an anti-settling agent, 94.5 parts of a modified thermal conductive filler, and 0.2 parts of a platinum catalyst;

[0095] The second component includes the following raw materials by mass: 2 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60 mPa·s, 1.5 parts of anti-settling agent, 94.5 parts of modified thermal conductive filler, 0.1 parts of inhibitor, 1 part of hydrogen-terminated polydimethylsiloxane with a hydrogen content of 0.36 wt%, and 0.9 parts of methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.18 wt%;

[0096] The modified thermal conductive filler includes the following raw materials by mass: 10 parts of spherical aluminum nitride with a particle size of 70 μm, 40 parts of spherical aluminum oxide with a particle size of 70 μm, 10 parts of aluminum nitride with a particle size of 50 μm, 30 parts of aluminum oxide with a particle size of 10 μm, 9.5 parts of aluminum oxide with a particle size of 5 μm, 0.2 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil, and 0.3 parts of single-end triethoxysilane-terminated polydimethylsilicone oil;

[0097] The anti-settling agent includes the following raw materials by mass: 35 parts of zinc oxide powder with a particle size of 1 μm, 35 parts of aluminum oxide powder with a particle size of 0.6 μm, 0.5 parts of single-end trimethoxysilane-terminated polydimethyl silicone oil, 0.5 parts of single-end triethoxysilane-terminated polydimethyl silicone oil, and 29 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60 mPa·s.

[0098] The preparation method of the above-mentioned potting glue comprises:

[0099] By mass, 10 parts of spherical aluminum nitride with a particle size of 70 μm, 40 parts of spherical aluminum oxide with a particle size of 70 μm, 10 parts of aluminum nitride with a particle size of 50 μm, 30 parts of aluminum oxide with a particle size of 10 μm, and 9.5 parts of aluminum oxide with a particle size of 5 μm were put into a high-speed mixer for mixing (the equipment speed was 10 Hz, and the time was 2 min), and 0.2 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil and 0.3 parts of single-end triethoxysilane-terminated polydimethylsilicone oil were added, and then dispersed and mixed at a high speed (the equipment speed was 25 Hz, and the time was 5 min) to obtain a modified thermal conductive filler;

[0100] By weight, 35 parts of zinc oxide powder with a particle size of 1 μm and 35 parts of aluminum oxide powder with a particle size of 0.6 μm were put into a high-speed disperser for mixing (the equipment speed was 10 Hz and the time was 2 min), 0.5 parts of single-end trimethoxysilane-terminated polydimethylsilicone oil and 0.5 parts of single-end triethoxysilane-terminated polydimethylsilicone oil were added, and then dispersed and mixed at a high speed (the equipment speed was 25 Hz and the time was 5 min), and the treated powder was added to 29 parts of terminal vinyl polydimethylsiloxane with a viscosity of 40-60 mPa·s, and dispersed evenly with a planetary mixer (stirring rate was 20 Hz, dispersion rate was 300 Hz, and stirring time was 1 h) to obtain an anti-settling agent;

[0101] 3.8 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60 mPa·s, 1.5 parts of an anti-settling agent, 94.5 parts of a modified thermally conductive filler, and 0.2 parts of a platinum catalyst were added into a reaction kettle by weight, and dispersed evenly with a planetary mixer (stirring rate of 30 Hz, dispersion rate of 800 Hz, stirring time of 1 h), and mixed to obtain a first component;

[0102] 2 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60 mPa·s, 1.5 parts of an anti-settling agent, 94.5 parts of a modified thermally conductive filler, 0.1 parts of an inhibitor, 1 part of a hydrogen-terminated polydimethylsiloxane with a hydrogen content of 0.36 wt%, and 0.9 parts of a methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.18 wt% were added into a reaction kettle, and dispersed evenly with a planetary mixer (stirring rate of 30 Hz, dispersion rate of 800 Hz, stirring time of 1 h), and mixed to obtain a second component;

[0103] The prepared first component and second component are mixed in a mass ratio of 1:1 for use.

[0104] Comparative Example 1

[0105] A potting adhesive is prepared by mixing a first component and a second component;

[0106] The first component includes the following raw materials by mass: 7.0 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60 mPa·s, 40 parts of spherical alumina with a particle size of 70 μm, 10 parts of alumina with a particle size of 40 μm, 20 parts of alumina with a particle size of 10 μm, 20 parts of alumina with a particle size of 5 μm, 0.2 parts of dodecyltrimethoxysilane, 0.3 parts of deoxytrimethoxysilane, and 0.2 parts of a platinum catalyst;

[0107] The second component includes the following raw materials by mass: 4.3 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60mPa·s, 1.3 parts of hydrogen-terminated polydimethylsiloxane with a hydrogen content of 0.18wt%, 1.5 parts of methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.18wt%, 40 parts of spherical alumina with a particle size of 70μm, 10 parts of alumina with a particle size of 40μm, 20 parts of alumina with a particle size of 10μm, 20 parts of alumina with a particle size of 5μm, 0.2 parts of dodecanetrimethoxysilane, 0.3 parts of deoxytrimethoxysilane, and 0.1 parts of an inhibitor.

[0108] The preparation method of the above-mentioned potting glue comprises:

[0109] By mass fraction, 7.0 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60 mPa·s, 40 parts of spherical alumina with a particle size of 70 μm, 10 parts of alumina with a particle size of 40 μm, 20 parts of alumina with a particle size of 10 μm, 20 parts of alumina with a particle size of 5 μm, 0.2 parts of dodecanetrimethoxysilane, 0.3 parts of deoxytrimethoxysilane, and 0.2 parts of a platinum catalyst are added into a reactor, dispersed evenly with a planetary mixer (stirring rate of 30 Hz, dispersion rate of 800 Hz, stirring time of 1 h), and mixed to obtain a first component;

[0110] 4.3 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 40-60 mPa·s, 1.3 parts of hydrogen-terminated polydimethylsiloxane with a hydrogen content of 0.18 wt%, 1.5 parts of methyl-terminated methylhydrogensiloxane with a hydrogen content of 0.18 wt%, 40 parts of spherical alumina with a particle size of 70 μm, 10 parts of alumina with a particle size of 40 μm, 20 parts of alumina with a particle size of 10 μm, 20 parts of alumina with a particle size of 5 μm, 0.2 parts of dodecanetrimethoxysilane, 0.3 parts of deoxytrimethoxysilane, and 0.1 parts of an inhibitor are put into a reaction kettle, dispersed evenly with a planetary mixer (stirring rate of 30 Hz, dispersion rate of 800 Hz, stirring time of 1 h), and mixed to obtain a second component;

[0111] The prepared first component and second component are mixed in a mass ratio of 1:1 for use.

[0112] The thermal conductivity, sedimentation time and viscosity of Examples 1-3 and Comparative Example 1 were tested respectively. The results are shown in Table 1:

[0113] Table 1 Thermal conductivity, sedimentation time and viscosity test results of Examples 1-3 and Comparative Example 1

[0114]

[0115] In summary, the embodiments provided in the present application not only have excellent thermal conductivity but also can effectively prolong the sedimentation time of the potting compound while ensuring a relatively low viscosity (below 10000 mPa·s).

[0116] The above embodiments are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to in detail.

[0117] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the interpretation of the attached claims includes the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present application.

[0118] Finally, it should be noted that in this specification, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or terminal device including the elements.

[0119] The above is a detailed introduction to an anti-settling and high thermal conductivity potting glue and its preparation method provided by the present application. The present specification uses specific examples to illustrate the principles and implementation methods of the present application. The above examples are only used to help understand the method and its core idea of ​​the present application. At the same time, for those skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present application.

Claims

1. A potting glue with high heat conductivity and anti-settling properties, characterized in that: The first component and the second component are mixed; The first component includes the following raw materials by mass: 2-8 parts of vinyl-terminated polydimethylsiloxane, 1-10 parts of anti-settling agent, 90-98 parts of modified thermal conductive filler and 0.1-1 parts of platinum catalyst; The second component comprises the following raw materials by mass: 1-6 parts of vinyl-terminated polydimethylsiloxane, 1-10 parts of anti-settling agent, 90-98 parts of modified thermal conductive filler, 0.1-1 parts of inhibitor, 1-6 parts of hydrogen-terminated polydimethylsiloxane and 1-6 parts of methyl-terminated methylhydrogensiloxane; The anti-settling agent comprises the following raw materials by weight: 50-75 parts of ultrafine powder, 0.2-2 parts of treating agent and 25-50 parts of vinyl-terminated polydimethylsiloxane; the particle size of the ultrafine powder is less than 1 μm.

2. The potting compound according to claim 1, characterized in that: The ultrafine powder includes at least one of silicon dioxide, glass fiber, aluminum oxide, aluminum hydroxide and zinc oxide.

3. The potting compound according to claim 1, characterized in that: The modified thermally conductive filler comprises the following raw materials by weight: 98-99.8 parts of thermally conductive filler and 0.2-2 parts of treating agent.

4. The potting compound according to claim 3, characterized in that: The thermally conductive filler includes at least one of aluminum oxide, aluminum nitride, aluminum hydroxide, zinc oxide and diamond.

5. The potting adhesive according to claim 1 or 3, characterized in that: The treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.

6. The potting compound according to claim 5, characterized in that: The treating agent includes at least one of y-(2,3-epoxypropoxy)propyltrimethoxysilane, y-methacryloxypropyltrimethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, and at least one of single-end trimethyl / ethoxysilane-terminated polydimethylsiloxane and polyether-modified polydimethylsiloxane.

7. The potting compound according to claim 1, characterized in that: The viscosity of the vinyl-terminated polydimethylsiloxane is 40-110 mPa·s, and the vinyl content is 0.9-2.1 wt %; the hydrogen content of the hydrogen-terminated polydimethylsiloxane is 0.1-0.36 wt %; and the hydrogen content of the methyl-terminated methylhydrogensiloxane is 0.1-0.36 wt %.

8. A method for preparing the potting compound according to any one of claims 1 to 7, characterized in that: include: The modified thermal conductive filler, the anti-settling agent, the vinyl-terminated polydimethylsiloxane and the platinum catalyst are stirred and mixed according to a proportion to obtain a first component; The modified thermal conductive filler, the anti-settling agent, the vinyl-terminated polydimethylsiloxane, the hydrogen-terminated polydimethylsiloxane, the methyl-terminated methylhydrogensiloxane and the inhibitor are stirred and mixed according to the proportion to obtain the second component.

9. The preparation method according to claim 8, characterized in that: Also includes: The thermal conductive filler and the treating agent are stirred and mixed according to a proportion to obtain a modified thermal conductive filler.

10. The preparation method according to claim 8, characterized in that: Also includes: The ultrafine powder, the treating agent and the vinyl-terminated polydimethylsiloxane are stirred and mixed according to a proportion to obtain an anti-settling agent.